Manajemen Pendirian Lembaga Pendidikan Anak Usia Dini - Nabila Aisyah Putri; Dewi Sapitri; Diana Yunita; Khoirunnisa Khoirunnisa; Eti Hadiati (Invention: Journal Research and Education Studies, 2025)
Early Childhood Education (PAUD) is an important foundation in character building and developing children's potential that determines the quality of future generations. This study aims to comprehensively analyze the management process of establishing PAUD institutions including planning, organizing, implementation, and evaluation stages, and identify factors influencing the success of PAUD establishment. The research method used is library research by examining books, national and international open-access journals, official government reports, and regulations related to PAUD establishment management. The results show that PAUD institution establishment management is a structured process involving four main stages. The planning stage includes community needs analysis, feasibility studies, vision-mission formulation, and budget projection. The organizing stage includes forming organizational structures, recruiting qualified educators, and preparing facilities according to standards. The implementation stage includes licensing processes, community socialization, and play-based learning implementation. The evaluation stage involves continuous monitoring of all PAUD operational aspects. PAUD establishment success is influenced by internal factors (organizer commitment, educator competence, facilities, financial management) and external factors (government support, community participation, socio-economic conditions). Main challenges include lack of regulatory understanding, licensing administrative complexity, limited qualified educators especially in remote areas, financial constraints, and minimal institutional management understanding. This research provides theoretical contributions to PAUD education management science development and practical guidance for prospective PAUD institution organizers.